Reabilitação do assoalho pélvico em pacientes com incontinência urinária pós prostatectomia radical - Andrade, Carla Elaine Laurienzo da Cunha [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Objective: To evaluate impact of rectal electrical stimulation in urinary continence and sexual function rehabilitation in patients undergone to radical prostatectomy. Methods: This randomized controlled clinical trial included patients in preoperative workup for radical prostatectomy. Were evaluated quality of life (ICIQ-SF), erectile function (IIEF-5), urinary symptoms (IPSS score), urinary loss (Pad Test 1 hour), and pelvic floor muscular strenght (Perineometry), in four moments: preoperative, postoperative follow-up of 1, 3 and 6 months. Patients were randomized in three groups (control, verbal guidance and electrical stimulation). The verbal guidance group were instructed by a physiotherapist to practice exercises to empowering pelvic floor after catheter removal. The electrical stimulation group undergone to 14 sesions of pelvic floor electrical stimulation, with 35Hz frequency, twice a week. Results: Between October 2010 and September 2013, were included 123 patients undergone to radical prostatectomy with mild, moderate or high urinary incontinence (Pad Test ≥ 3 gr). These patients were randomized: control group (n:40), verbal guidance (n:41) and electrical stimulation (n:42). Demographics and pathological variables were similar between the groups. The analysis of the variables QoL, urinary symptoms, erectile function and perineometry did not demonstrate differences between the groups analysed. The Pad Test values in 6 months follow-up had no statistical significance between the groups (median were: 1,0gr (0-23,0); 1,0gr (0-78,0) and 1,0gr (0-18,0), respectively. Conclusion: QoL, urinary symptoms, erectile function and muscular strength do not show a better rehabilitation in electrical stimulation group in our study population. Pelvic floor electrical stimulation did not show impact in urinary continence after radical prostatectomy

Objetivos: Avaliar o impacto da eletroestimulação retal na recuperação da continência urinária em pacientes submetidos à prostatectomia radical. Método: Ensaio clínico, randomizado e controlado, no qual foram incluídos pacientes no período pré operatório de prostatectomia radical. Foram avaliados a qualidade de vida (pelo questionário específico ICIQ-SF), os sintomas urinários (pelo escore IPSS), a função erétil (pelo instrumento específico IIEF-5), a perda urinária (por Pad Test de 01 hora) e a força muscular do assoalho pélvico (por perineometria), em quatro momentos: pré operatório, 01º, 03º e 06º meses pós operatórios. Os pacientes foram randomizados em três grupos (controle, orientação e eletroestimulação + exercícios perineais). O grupo orientação recebeu instruções de uma fisioterapeuta para realização de exercícios de fortalecimento do assoalho pélvico, após a retirada da sonda vesical. O grupo eletroestimulação realizou 14 sessões de eletroestimulação do assoalho pélvico, com frequência de 35Hz, duas vezes por semana e tambpem recebeu orientações para exercícios perineais. Resultados: No período de outubro de 2010 à setembro de 2013, 123 pacientes submetidos a Prostatectomia Radical, com Incontinência Urinária Leve (Pad Test ≥ 3 gramas), Moderada ou Grave foram randomizados para o grupo controle (n:40), orientação (n:41) e eletroestimulação + exercícios perineais (n:42). Não houve diferença estatisticamente significativa entre os grupos em relação às variáveis clínicas e patológicas. Nas medidas de qualidade de vida, sintomas urinários e função erétil, a realização de eletroestimulação não demonstrou impacto na população estudada. O valor de perda urinária (medido pelo Pad Test), ao final do seguimento, foi similar e não houve diferença estatística: 1,0 (0,0-23,0) vs (1,0 (0,0-78,0) vs 1,0 (0,0-18,0), respectivamente. Em relação à perineometria,...
Keywords: Diafragma da pelve; Incontinência urinária; Estimulos eletricos; Prostatectomia; Próstata - Câncer; Prostatectomy